A Place at the Multicultural Table : The Development of an American Hinduism - Kurien, Prema A., 1963- (Book collections on Project MUSE., 2007)
Multiculturalism in the United States is commonly lauded as a positive social ideal celebrating the diversity of our nation. But, in reality, immigrants often feel pressured to create a singular formulation of their identity that does not reflect the diversity of cultures that exist in their homeland. Hindu Americans have faced this challenge over the last fifteen years, as the number of Indians that have immigrated to this country has more than doubled. In A Place at the Multicultural Table, Prema A. Kurien shows how various Hindu American organizations--religious, cultural, and political--are attempting to answer the puzzling questions of identity outside their homeland. Drawing on the experiences of both immigrant and American-born Hindu Americans, Kurien demonstrates how religious ideas and practices are being imported, exported, and reshaped in the process. The result of this transnational movement is an American Hinduism--an organized, politicized, and standardized version of that which is found in India. This first in-depth look at Hinduism in the United States and the Hindu Indian American community helps readers to understand the private devotions, practices, and beliefs of Hindu Indian Americans as well as their political mobilization and activism. It explains the differences between immigrant and American-born Hindu Americans, how both understand their religion and their identity, and it emphasizes the importance of the social and cultural context of the United States in influencing the development of an American Hinduism.